Advancing higher education on sustainable land use: designing socioscientific inquiry-based learning units on oil palm cultivation - Matthiesen, Finn Kristen; Dischereit, Jacqueline; Mataniari, Raissa; Setiajiati, Fitta; Suparta, I Nengah; Bögeholz, Susanne (Frontiers in Education, 2025)
Land-use change driven by the global oil palm boom has widespread environmental and socioeconomic consequences. Recent scientific research offers strategies to mitigate negative effects of oil palm cultivation. This Curriculum, Instruction, and Pedagogy article presents a design-based research (DBR) approach to increase students’ knowledge and interest in interdisciplinary scientific research for sustainable oil palm cultivation. The land-use research addressed in this DBR is based on the international Collaborative Research Centre 990 “Ecological and Socioeconomic Functions of Tropical Lowland Rainforest Transformation Systems” (EFForTS). It focused on sustainable land-use change in Indonesia. Through a collaborative design process, researchers and educators from Indonesian and German universities designed two educational units on oil palm cultivation as a socioscientific issue for Indonesian higher education, specifically for science teacher education and forestry study programs. We systematically analyzed curricular needs, objects of recent scientific research, teaching and learning frameworks, and evaluation approaches to determine design principles. A pre-post-follow-up evaluation (N = 943) showed that the units, when integrated into curricular courses, increased and sustained students’ self-reported knowledge and interest, with improvements from pilot to implementation cycles. The formative and summative evaluations indicated positive ratings for instructional design quality, while also identifying areas for future improvement. Our DBR focused on Indonesian higher education, but the evaluation and reflection findings suggest that our approach can be adapted to a wide range of educational contexts and environmental socioscientific issues, also beyond Indonesia. Our DBR serves as a transferable approach for making scientific research topics, methods, and findings accessible and interesting to students, thereby contributing to the preparation of future change agents for sustainable land use at both local and global scales.